La Implementación de Secuencias de Movimiento como Estrategia Pedagógica para Mejorar la Coordinación de Movimientos de los Estudiantes del Énfasis “Aprendiendo a través del Arte” del Colegio Distrital la Amistad - Gómez Cortés, Rubén Darío (Universidad Antonio Nariño, 2024)
This document presents a research carried out within the teaching practice process of the Bachelor's Degree in Basic Education with Emphasis in Artistic and Cultural Education at the Antonio Nariño University, about the pedagogical strategies related to the way in which body formation in Movement sequences can enhance the development of motor coordination skills in a population of 10th and 11th grade students within the artistic education emphasis of the IED Amistad in the 8th Kennedy Town, in Bogota, Colombia.